In Silico Investigation of γ-Sitosterol Isolated from the Ethanol Extract of Artocarpus camansi Leaves as a Sunscreen Agent - Nasution, Rosnani; Azura, Rafna; Bahi, Muhammad; Maulydia, Nur Balqis; Bastian, Reza Akbar; Hilda, Michelia Mutiara; Marianne, Marianne (Universitas Gadjah Mada, 2025)
The activity test of sunscreen lotion from the ethanolic extract of Artocarpus camansi leaves was carried out. The activity of sunscreen lotion as sun protecting factor (SPF) is ranging from 28.716 ± 0.1557 to 29.740 ± 0.1360, while the SPF of pure compound is 28.483 ± 0.1422. The type of lotion is water in oil (w/o) with viscosity and pH values in the range of 3057.1–5001.1 cP and 6.86–7.89, respectively. The viscosity and pH values obtained were following the standard SNI 16-4399-1996. The value of dispersion is in the range of 4.60–6.90 cm, while the value of adhesion is in the range of 14.55–25.03 s. The pure compound is thought to be γ-sitosterol by analysis of its molecular weight similarity and positive ion fragment m/z with a melting point of 147 °C. From the molecular docking, it is known that γ-sitosterol has the highest binding affinity value of −7.4 and −8.2 kcal/mol to human neutrophile collagenase (PDB ID: 1BZS) and fibroblast collagenase-1 (PDB ID: 966C), respectively. The presence of active compounds in the ethanolic extract of A. camansi lotion can support the activity of the SPF so that it can be used as a sunscreen formula.